PENGUATAN WAWASAN KEBANGSAAN DI LINGKUNGAN SMA NEGERI 17 JAKARTA DALAM MENGHADAPI GLOBALISASI DAN DIGITALISASI - Sitabuana, Tundjung Herning; Sanjaya, Dixon; Amri, Ibra Fulenzi; Goldwen, Filshella (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
The globalization and digitalization due to technological advances has led society to a chaotic situation. Distinction between truth and lies or honesty and dishonesty has become biased. This is era of false truth and post truth. This situation endangers the unity of Indonesian nation. This vulnerability has the potential to occur in younger generation who are largest in number but the intensity of interaction with local cultural values is minimal. The younger generation has experienced a shift in value and ethical behavior that has been degraded. This Community Service’s Team (PKM Team) intends to provide legal education to students regarding